Peranan Advokat Terhadap Tersangka Yang Diancam Hukuman Diatas 5 (Lima) Tahun - HJ. Jauhariah (PRANATA HUKUM, 2013)
If the suspect or the alleged indictment or charged with a criminal offense punishable death penalty or fifteen years or more. In the second category of punishment question whether they can afford it or not. If they are able to finance themselves and may choose legal counsel wants. If you are not able to provide and pay for itself, at the time the obligation arises for the officials concerned to appoint legal counsel for the accused or defendant. An obligation for the concerned officials appoint counsel for the accused or the accused, suspended on two conditions, namely the suspect or defendant is not able to provide their own legal counsel and the threat of criminal penalties are concerned five years or more.